Polyvinyl alcohol-based biocomposites and bionanocomposites - P. M., Visakh; Nazarenko, Olga (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2023)
Polyvinyl Alcohol-Based Biocomposites and Bionanocomposites Serves as a one-stop reference resource for important research accomplishments in the area of polyvinyl alcohol-based biocomposites and bionanocomposites. Many recent research accomplishments in the area of polyvinyl alcohol (PVA)-based biocomposites and bionanocomposites are summarized in this book. In it, the editors discuss as many topics as possible on the most recent state-of-the-art developments regarding these biocomposites and bionanocomposites, the challenges faced when using them, and their future prospects. In addition to providing a biodegradation study of them, their significance and applications are also discussed, along with practical steps toward their commercialization. Moreover, PVA/cellulose-based and PVA/starch-based biocomposites and bionanocomposites are discussed, along with the biomedical applications of PVA-based composites and nanocomposites, and PVA-based hybrid interpolymeric complexes and their applications. Audience This book will be a very valuable reference source for polymer researchers, materials scientists, biochemists, engineers, graduate and postgraduate students working on polymers, composites, and nanocomposites, especially in the area of polyvinyl alcohol-based bionanocomposites.